AM1 Study of N-2-Acetylaminofluorene bonded to Deoxyguanosine at the Minor Adduct Site - Besson, M. (Kluwer Academic Publishers, 2004)
We have computed the total energy as a function of six important torsion angles of the carcinogen N-2-acetylaminofluorene (AAF) bonded to thenitrogen N2 of deoxyguanosine using the semiempirical quantum mechanical method AM1. One global minimum and one local minimum are found separated by a modest barrier. We have computed the normal-mode frequencies of the relevant torsional motions and have determined the rate of conversion betweenthe two minima.